2021
DOI: 10.1111/aab.12670
|View full text |Cite
|
Sign up to set email alerts
|

Current status and perspectives on the role of polyamines in plant immunity

Abstract: Polyamines are low molecular weight amines, with versatile and essential functions during the lifespan of prokaryotes and eukaryotes. Modulation of polyamine metabolism under biotic stress has attracted a great deal of interest; however, the precise functions of these amines in plant defence responses to pathogen attack are still poorly understood. Herein we summarise and review important aspects of the regulation of polyamine biosynthesis, catabolism and conjugation under biotic stress that might contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 112 publications
0
17
0
1
Order By: Relevance
“…Polyamines are small aliphatic amines found in all living cells. Put, Spd, and Spm are major components in plants and play vital roles in plant growth, development, and stress response ( Pál et al, 2015 ; Ghosh et al, 2021 ; Gonzalez et al, 2021 ). The levels of PAs increase considerably in response to cold stress ( Amini et al, 2021 ; Jiao et al, 2021 ; Wang et al, 2021 ), and a cold-tolerant rice cultivar showed a greater accumulation of PAs than the sensitive cultivars ( Sheteiwy et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines are small aliphatic amines found in all living cells. Put, Spd, and Spm are major components in plants and play vital roles in plant growth, development, and stress response ( Pál et al, 2015 ; Ghosh et al, 2021 ; Gonzalez et al, 2021 ). The levels of PAs increase considerably in response to cold stress ( Amini et al, 2021 ; Jiao et al, 2021 ; Wang et al, 2021 ), and a cold-tolerant rice cultivar showed a greater accumulation of PAs than the sensitive cultivars ( Sheteiwy et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemically, the synthesis and decomposition of PAs in cells are relatively well characterized [for good reviews, refer to Wang et al (2019) and Gonzalez et al (2021) ]. The biosynthesis of PAs can be divided into two major steps ( Figure 1 ).…”
Section: Polyamine Generation and Catabolismmentioning
confidence: 99%
“…Regarding cellular PA-homeostasis, besides free soluble and non-covalently conjugated forms, PAs may also bind to proteins and other molecules to protect the macromolecules, regulate transporter/channel activity and gene expression, or interact with some hormones. This metabolism presentation of PAs in the plant is partially adapted from the studies by Gonzalez et al (2021) and Spormann et al (2021) .…”
Section: Polyamine Generation and Catabolismmentioning
confidence: 99%
“…Polyamines are regulators of many physiological processes in plants, including cellular differentiation, embryogenesis, germination, organogenesis, flower development, pollen germination and growth, fruit maturation and delayed senescence (Anwar et al, 2019;Benkő et al, 2020;Mattoo and Sobieszczuk-Nowicka, 2018;Mustafavi et al, 2018;Pagano et al, 2019;Takahashi and Kakehi, 2010). In addition, PAs exert crucial roles in the abiotic and biotic stress responses that have been well documented in literature reviews (Alcázar et al, 2010;Chen et al, 2019;Gill and Tuteja, 2010;Gonzalez et al, 2021;Jiménez-Bremont et al, 2014;Minocha et al, 2014;Paschalidis et al, 2019;Tsaniklidis et al, 2020). Due to its biological implications, PA metabolism is subjected to a finetuned regulation.…”
Section: Introductionmentioning
confidence: 99%